Tumor Analyses Reveal Squamous Transformation and Off-Target Alterations As Early Resistance Mechanisms to First-line Osimertinib in EGFR-Mutant Lung Cancer - Schoenfeld, Adam J. (Clin Cancer Res, 2020)
PURPOSE: Patterns of resistance to first-line osimertinib are not well-established and have primarily been evaluated using plasma assays which cannot detect histologic transformation and have differential sensitivity for copy number changes and chromosomal rearrangements. EXPERIMENTAL DESIGN: To characterize mechanisms of resistance to osimertinib, patients with metastatic EGFR-mutant lung cancers who received osimertinib at Memorial Sloan Kettering and had next-generation sequencing performed on tumor tissue before osimertinib initiation and after progression were identified. RESULTS: Among 62 patients who met eligibility critieria, histologic transformation, primarily squamous transformation, was identified in 15% of first-line osimertinib cases and 14% of later-line cases. Nineteen percent (5/27) of patients treated with first-line osimertinib had off-target genetic resistance (2 MET amplification, 1 KRAS mutation, 1 RET fusion, and 1 BRAF fusion) whereas 4% (1/27) had an acquired EGFR mutation (EGFR G724S). Patients with squamous transformation exhibited considerable genomic complexity; acquired PIK3CA mutation, chromosome 3q amplification and FGF amplification were all seen. Patients with transformation had shorter time on osimertinib and shorter survival compared to patients with on-target resistance. Initial EGFR sensitizing mutation, time on osimertinib treatment and line of therapy also influenced resistance mechanism that emerged. The compound mutation EGFR S768 + V769L and the mutation MET H1094Y were identified and validated as resistance mechanisms with potential treatment options. CONCLUSION: Histologic transformation and other off-target molecular alterations are frequent early emerging resistance mechanisms to osimertinib and are associated with poor clinical outcomes.